CLEAN TECHNOLOGIES IN TANNERY - СКИБА, М. Є. (Technologies and Engineering, 2025)
Purpose. To summarize and systematize the information provided in the scientific and technical literature on the use of clean technologies in the production of genuine leather, which do not have or reduce the permanent negative impact on the environment. Methodology. To ensure a systematic approach to obtaining, analysing and interpreting the results, the methods of research, analysis, coordination, generalization and systematization were used. Findings. Based on the analysis of scientific and technical literature of recent years, the essence and significance of resource-saving and environmentally friendly technologies for the sustainable development of the industry are revealed. Modern production of genuine leather involves the processing of natural raw materials using large amounts of water, electricity and chemicals. The latter leads to the formation of a large volume of solid waste, significant pollution of industrial wastewater and forces us to actively seek ways to reduce the negative impact of industrial activities of industry enterprises on the environment. The analysis of the literature reflects the growth of research and development in this area with an emphasis on sustainable chemistry as the basis for creating clean technologies and sustainable development of the industry. The need to save natural resources expands the use of natural and nanomaterials at different stages of tannery. Particular attention should be paid to the creation of enzyme preparations, the introduction of which will reduce the use or completely eliminate a number of environmentally hazardous materials and positively affect the environmental state, both at the enterprises themselves and around them. More efficient technologies for processing skins at different stages of the technological cycle, innovative methods of wastewater treatment, more efficient waste recycling techniques are proposed. The ideal approach to moving the industry closer to a circular economy is to use waste from its own production to tannery. Originality. Information has been generalized and systematized on approaches to the use of clean technologies at all stages of the production of genuine leather - from raw materials in the form of animal skin to a wide range of finished products - aimed at adhering to the principles of resource conservation and reducing the harmful environmental impact on the environment both at an individual enterprise and in the industry as a whole. Practical value. The results of studying and organizing theoretical and practical achievements in the leather production of clean technologies will contribute not only to the expansion of knowledge about improving the methods of manufacturing natural leather in the direction of reducing environmental pollution due to the production activities of industry enterprises, but also to the advancement of scientific, technical and technological development of the industry to a higher level, namely the creation of circular technologies.